Does a six-week intervention with added respiratory dead space volume in swimming improve haematological and immunological status? - Szczepan, S.; Michalik, K.; Hebisz, R. (Baltic Journal of Health and Physical Activity, 2022)
Background: The aim of study was to investigate if differences appeared in haematological parameters after a 6-week moderate-intensity swimming intervention with added respiratory dead space volume (ARDSV) in recreational swimmers.